Guess who's coming to breakfast - Wiseman, Peter; Barret, Neil; Hogart, Sue (Bendigo, Vic, : Video Education Australasia, 1991)
Discusses the nutritional importance of a good breakfast and criteria for choosing it. Advises chronic avoiders on ways to learn to like breakfast
Writers, Neil Barrett, Peter Wiseman ; camera, Avid Lovell, Peter Wiseman ; editor, producer, Peter Wiseman
Narrator : Sue Hogar